Repositioning Spiritualism as an Educator's Competence : Christian Education's Efforts to Boost Lecturer Professional Competence - Simamora, Dame Taruli (LP. Ma'arif Janggan Magetan, 2022)
The implementation of Christian values, especially talking about spirituality, is the responsibility of lecturers in carrying out their responsibilities, by reflecting on the Great Teacher. The importance of aspects of spirituality is owned by educators because Christian education views education as an effort to change students for the better. Ironically, this view is actually weakened by the idea that spirituality is something personal, implemented in the relationship between created beings and their creators, so cannot be used as a standard. This study aims to examine lecturers' understanding of spiritual competence towards improving lecturer professionalism. This research is a quantitative research, with a survey approach. Data was collected through a questionnaire containing 40 questions related to spirituality and professionalism of lecturers. The population studied was lecturers at state religious institutes in Western Indonesia, with a sample of 60 people. The data were analyzed by simple linear regression. Through field tests, it was concluded that understanding of spiritual competence on lecturer professionalism is 35%. It is necessary for educators to implement good personality and divine character, all of which are integrative parts of his vocation as servants. The quality of education received by students is increasing, as an impact of increasing the professionalism and spiritualism of educators.